A Slavic Cremation Grave from Lobor (Archaeologia Adriatica, 2009)
During archaeological excavations at the site of Lobor, at the pilgrimage church of Our Lady of the Mountain (Majka Božja Gorska), an urn with cremated remains of a deceased individual was discovered in 2009. It was found to the south of the existing church at the place where the remains of a wooden church had been discovered, which had been excavated completely. While emptying the postholes of the wooden church, the remains were found of an upsidedown pottery vessel containing ash, soot, and bones. Other than individual fragments of pottery vessels, no strata were found during the archaeological excavations that could be dated before the beginning of the 9th century. In general few fragments of medieval pottery vessels were found, and those few were fairly tiny. The established remains of an adult male in the pottery vessel confirm that it served as an urn. In addition to the human remains found in the vessel, there were also remains of cattle, sheep or goat, deer, and pig. Individual small pieces of animal bone were evidently gathered and placed together in the same vessel after the feast in honor of the deceased. The varied types of animals that were consumed at the funeral indirectly indicate the wealth of the family of the deceased. This must have been a well-to-do member of the Slavic community. This was also indicated by the very well-made vessel that served as the urn. Several fragments of tiny bronze objects were found in the layer surrounding the urn, but only theoretically could they belong to the contents of the urn. Several variously decorated bone objects were found in the layer of the ruins of the wooden church. The urn, as was already noted, was not placed at the base of the posthole, but rather somewhere in its middle. Hence it could not have arrived in this position during the erection of the church prior to the placement of the wooden beam. Soot and ash and burnt animal bones were found everywhere around the posthole. It is very probable that on the occasion of building the wooden church, dated to the very beginning of the 9th century, the cremation grave with the urn was damaged by the placement of the post just next to it. When that church was demolished and the wooden posts were removed, the urn fell into the empty hole. The church in fact was not destroyed immediately after the construction of the three-aisled basilica, rather the basilica and the wooden church almost certainly stood until the middle of the 10th century adjacent to one another. Two silver denarii of the Hungarian King Stephen I, found in the fill between the graves located in a layer above the wooden church perhaps indicate the period of it’s demolition. Not a single grave, other than the previously mentioned grave of a young girl in the apse of the church, found in the layers above the wooden church, can be dated prior to the 13th century. The wooden church was built next to the Early Christian one, but in a place occupied by an earlier pagan cemetery. The Slavs had placed their graves around the site of the Early Christian church and its ruins. Not a single cremation grave has been found in situ due to the construction of the wooden church, and probably the building of the three-aisled basilica, as well as the long burial tradition that took place at the same site. The remains of the only urn discovered so far were found thanks to the fact that it had fallen into a posthole of the wooden church. This preserved it from possible later damage. The cremation grave from Lobor should also be dated to the end of the 8th or beginning of the 9th century. The circumstances of the find allow us to conclude (the urn having been dislocated in the area of a wooden Carolingian church from the beginning of the 9th century) that this was very probably one of the last such burials at the cemetery at Lobor. In the very next generation, given the changed political conditions under the influence of the Frankish missionaries, the Christian inhumation burial ritual became predominant. The dislocated urn from Lobor is just one more contribution to knowledge about the earliest burial customs of the Slavs in the Pannonian plain, but also further. An uninterrupted continuity of burial from the 9th to the 19th centuries had already been discovered at the site. It is now evident that the Christian stratum of the 9th century was preceded by a pagan burial ritual consisting of the cremation of the deceased and the placement of his or her remains in an urn.
Keywords: early Slavs; Pannonian Slavs; cremation grave; urn; Lobor